Chemical, antifungal, insecticidal and antioxidant studies on curcuma longa essential oil and its oleoresin - Singh, Gurdip (2005)
GC and GC-MS analysis of essential oil of Curcuma longa showed the presence of 32 components accounting for the 83.0% of the total amount. ar-turmerone (49.14%) was found as a major component followed by alpha-turmerone (11.59), ar-curcumene (3.83), beta-caryophyllene (2.79), alpha-zingiberene (2.61), terpinolene (2.26). The analysis of oleoresin showed the presence the 27 components accounting for 71.41% of the total amount. A mixture (14.07%) of ar-turmerone (55%) and zingerone (45%) was found as a major components followed by beta-sesquiphellandrene (9.29), ar-curcumene (9.04), linoleic acid (7.11), alpha-zingiberene (5.80), alpha-turmerone (5.14), beta-caryophyllene (4.84), beta-bisabolene (3.94); alpha-humulene (2.89), palmitic acid (2.64), alpha-atlantone (1.78. The essential oil possesses statistically significant antifungal as well as insecticidal character whereas, the oleoresin has been proved to be better antioxidant for rapeseed oil.